2015
DOI: 10.3892/ijmm.2015.2089
|View full text |Cite
|
Sign up to set email alerts
|

CAP1 is overexpressed in human epithelial ovarian cancer and promotes cell proliferation

Abstract: Adenylate cyclase-associated protein 1 (CAP1) regulates both actin filaments and the Ras/cAMP pathway in yeast, and has been found play a role in cell motility and in the development of certain types of cancer. In the present study, we investigated CAP1 gene expression in human epithelial ovarian cancer (EOC). Western blot analysis and immunohistochemistry were performed using EOC tissue samples and the results revealed that CAP1 expression increased with the increasing grade of EOC. In the normal ovarian tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…It is interesting to note that the expression level of hsa-miR-1, which shares a seed sequence with SFVmfu-miR-S7-5p, was down-regulated in various types of cancers (Liu et al, 2015;Han et al, 2017;Korde et al, 2017). The upregulation of CAP1 has been observed in several solid tumors, such as ovarian cancer, breast cancer (Xie et al, 2014;Hua et al, 2015;Hasan and Zhou, 2019), and rhabdomyosarcoma from which the TE671 cell line is derived (Rao et al, 2010). Rhabdomyosarcoma is also known to have a reduced expression level of hsa-miR-1, which suppresses CAP1 expression (Vinther et al, 2006;Rao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the expression level of hsa-miR-1, which shares a seed sequence with SFVmfu-miR-S7-5p, was down-regulated in various types of cancers (Liu et al, 2015;Han et al, 2017;Korde et al, 2017). The upregulation of CAP1 has been observed in several solid tumors, such as ovarian cancer, breast cancer (Xie et al, 2014;Hua et al, 2015;Hasan and Zhou, 2019), and rhabdomyosarcoma from which the TE671 cell line is derived (Rao et al, 2010). Rhabdomyosarcoma is also known to have a reduced expression level of hsa-miR-1, which suppresses CAP1 expression (Vinther et al, 2006;Rao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CAP1 showed higher gene expression levels in both significant CAD and nonsignificant CAD groups compared to the CG. Overexpression of CAP1 was found in many types of cancers [16][17][18], and considering that cell motility is one of the pivotal roles of CAP proteins [9], it seems that overexpressed CAP1 has a role in tumour invasion and metastasis, which was associated with the poor outcome of patients [17,18]. However, CAP1 has never been evaluated in patients with CAD in the context of resistin receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al showed that CAP1 was up-regulated and predicted brain metastasis and poor survival in non-small cell lung cancer [24] . Hua et al reported that CAP1 expression was induced, associated with Ki67 expression and poor outcome in epithelial ovarian cancer [25] . In HCC, high expression of CAP1 was correlated with unfavorable prognosis and promoted tumor metastasis [26] .…”
Section: Discussionmentioning
confidence: 99%